2023
DOI: 10.1007/s11259-023-10172-4
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial resistance genes in a golden jackal (Canis aureus L. 1758) from Central Italy

Abstract: In recent years an increasing interest has been focused on the contribution of wildlife in ecology and evolution of the antimicrobial resistance (AMR). The aim of this study was to molecularly investigate the presence of antimicrobial resistance genes (ARGs) in organ samples from a golden jackal (Canis aureus) found dead in the Marche region (Central Italy). Samples from lung, liver, spleen, kidney, and intestine were investigated by PCRs targeting the following genes: tet(A), tet(B), tet(C), tet(D), tet(E), t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Among wild animals, those with high ecological plasticity, such as the ability to survive in numerous different contexts, the wide territorial dispersion and the predatory attitude, might be indicators and/or vectors of AMR environmental contamination. In this regard, recent studies showed the presence of antimicrobial-resistant bacteria or ARGs in Iberian ( Canis lupus signatus ) and Apennine ( Canis lupus italicus ) wolves (Simões et al 2012 ; Gonçalves et al 2012 ; Smoglica et al 2020 , 2023a ) as well as in golden jackals in Italy (Di Francesco et al 2023b ).…”
Section: Introductionmentioning
confidence: 99%
“…Among wild animals, those with high ecological plasticity, such as the ability to survive in numerous different contexts, the wide territorial dispersion and the predatory attitude, might be indicators and/or vectors of AMR environmental contamination. In this regard, recent studies showed the presence of antimicrobial-resistant bacteria or ARGs in Iberian ( Canis lupus signatus ) and Apennine ( Canis lupus italicus ) wolves (Simões et al 2012 ; Gonçalves et al 2012 ; Smoglica et al 2020 , 2023a ) as well as in golden jackals in Italy (Di Francesco et al 2023b ).…”
Section: Introductionmentioning
confidence: 99%